La Dynamique du Système Socio-écologique dans la Concession Forestière des Communautés Locales de la Rivière Mbali en République Démocratique du Congo: Implication pour la Conservation du Bonobo (Pan Paniscus) - Valentin Omasombo Wotoko; Jean Malekani; Julien Punga; Jean-Philippe Cherel; Jean-Christophe Bokika (European Scientific Journal, ESJ, 2023)
Cette étude a porté sur l’analyse de la dynamique socio-écologique de la Concession Forestière des Communautés Locales de la Rivière Mbali et ses implications sur la conservation du bonobo. L’objectif est de dégager la problématique générale de la conservation du bonobo à travers l’évaluation de la socio-démographie des ménages et l’examen des modes d’utilisation des terres et d’extraction des ressources. L’observation participative, les interviews sur questionnaire ouvert, des entretiens informels et les focus group ont été utilisés pour collecter les données. Les résultats de l’étude montrent que les communautés locales de la concession forestière sont intimement liées à la forêt qu’elles partagent avec le bonobo. Elles en extraient les ressources naturelles, tant pour l’autoconsommation que pour leur économie. Dans cette zone, la chasse aux bonobos est interdite par un tabou alimentaire. L’agriculture itinérante sur brûlis et la collecte des produits forestiers non ligneux sont les principales activités de subsistance et sources de revenus. Avec une population locale en augmentation (la taille de ménage est de l’ordre 7 personnes), toutes ces activités peuvent avoir un impact très négatif sur les populations de bonobos si elles ne sont pas menées d’une manière durable. The disturbance of the environment is at the origin of the destruction of the habitats, it contributes to the loss of the biodiversity and is one of the causes of the change of the flora in a locality. It therefore leads to the transformation of plant associations. The main objective of this study is to research the plant associations in the Banco National Park following village plantations and silvicultural trials due to the search for a methodology specific to African silviculture. To do this, the phytosociological characterization of the former treatment sites and the forest reserve was carried out. The method used is that of synusial phytosociology. The 91 surveys (82 in the former silvicultural treatment sites and 9 in the forest reserve) made it possible to identify 337 species of plants divided into 65 families and 268 genera. The dendrogram resulting from the ascending hierarchical classification of the readings revealed three syntaxa, two of which essentially consist of the readings of the old treatment sites and one of the readings of the forest reserve. No syntaxon contains all the characteristic species of the Turraeantho-Heisterietum association. However, in two syntaxa, the proportion of characteristic species of this association is greater than 50%. 70.59% in the syntaxon to Tarrietia utilis and Cola heterophylla (syntaxon from secondary forests), 52.94% in the syntaxon to Cola chlamydantha and Drypetes chevalieri (syntaxon from the forest reserve). While in the Dacryodes klaineana and Pleiocarpa mutica syntaxon (secondary forest syntaxon), 41% of these characteristic species were recorded. Species characteristic of other forest formations are also poorly represented in the syntaxa (less than 40%). It therefore emerges from this study that Banco National Park remains a forest with Turraeanthus africanus and Heisteria parvifolia.